Heating Rate Behaviour Pyrolysis of Empty Fruit Bunches : Kissinger Kinetic Analysis - Rezki, Amelia Sri; Wulandari, Yeni Ria; Hanifah, Windia; Oktaviani , Lahara (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Biomass waste such as Empty Fruit Bunches (EFB), a byproduct of palm oil production in Indonesia, represents a promising renewable energy resource. Pyrolysis, a thermochemical conversion process, transforms this waste into valuable products and energy sources. This study uses the Kissinger kinetic model to investigate how a stepwise heating rate analysis, under both catalytic and non-catalytic conditions, influences the pyrolysis behaviour of EFB. Pyrolysis experiments were conducted in a batch reactor at 300 °C, 350 °C, and 400 °C, with and without adding a catalyst (aluminium white) at a 1:2 catalyst-to-feedstock ratio. Heating rates were calculated at 10 °C intervals, and the activation energy (Ea) was determined using the Kissinger kinetic model. The results indicate that, with the presence of a catalyst, the heating rate increases with temperature, while without a catalyst, the rate tends to decrease. Moreover, the catalyst substantially reduces the activation energy, from 12.046 kJ/mol (non-catalytic) to 10.957 kJ/mol (catalytic), indicating its effectiveness in enhancing thermal decomposition and facilitating pyrolysis with lower energy requirements.